2019
DOI: 10.1007/s11136-019-02175-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and mortality in patients with pulmonary embolism: a prospective cohort study in seven European countries

Abstract: Purpose Little is known about the quality of life following pulmonary embolism (PE). The aim of the study was to assess the 12-month illness burden in terms of health-related quality of life (HrQoL) and mortality, in relation to differences in patient characteristics. Methods The PREFER in VTE registry, a prospective, observational study conducted in seven European countries, was used. Within 2 weeks following an acute symptomatic PE, patients were recruited and followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 27 publications
2
58
1
3
Order By: Relevance
“…One-year mortality was 25% among our PE patients whereas it was 8.1% for PE in Europe, ranging from 1.4% in Germany, Switzerland, and Austria to 16.8% in Italy. Mortality differed between patients with active cancer (42.7%) and those without (4.7%) [10]. Our data showed that the readmission rates for both DVT and PE and one-year mortality was significantly higher in our population in comparison with European countries.…”
Section: Discussioncontrasting
confidence: 47%
“…One-year mortality was 25% among our PE patients whereas it was 8.1% for PE in Europe, ranging from 1.4% in Germany, Switzerland, and Austria to 16.8% in Italy. Mortality differed between patients with active cancer (42.7%) and those without (4.7%) [10]. Our data showed that the readmission rates for both DVT and PE and one-year mortality was significantly higher in our population in comparison with European countries.…”
Section: Discussioncontrasting
confidence: 47%
“…In addition, questionnaires were administered after 4 months and 10 years from the index PE event [14]. The prospective, observational, international PREFER study investigated the QoL of 1399 patients with PE using the EQ-5D-5L questionnaire‚-with a reported score of 0.71 ± 0.27 at the time of event [30]. Only 120 patients (8.6%) in this study had a diagnosis of cancer and disease-specific QoL questionnaires were not utilized.…”
Section: Discussionmentioning
confidence: 99%
“…However, at one year the HRQoL of the study population was comparable to that of the general population, contrasting other studies by indicating normalisation of HRQoL within one year 8 . A recently published study based on the data from the prospectively designed PREFER registry 191 reported a reduced HRQoL, as assessed by the EQ-5D, in 1399 PE patients compared to that of the general population 192 . In this study, improvement of HRQoL overtime was also observed.…”
Section: Paper IImentioning
confidence: 99%
“…Although, this improvement was mainly driven by the surviving patient population. In addition, they reported several comorbidities as being significant determinants of HRQoL 192 . Nevertheless, this particular topic has been a major subject of debate in which some suggest the impaired HRQoL is caused by comorbidities and/or deconditioning 7 , whereas others argue that possible associations with the PE event itself cannot be ruled out 157 .…”
Section: Paper IImentioning
confidence: 99%